An automated reminder for perioperative glucose regulation improves protocol compliance. (June 2016) - Polderman, Jorinde A.W.; de Groot, Fleur A.; Zamanbin, Alaleh; Hollmann, Markus W.; Holleman, Frits; Preckel, Benedikt; Hermanides, Jeroen
Highlights: Automated reminders are an effective strategy to improve protocol compliance. Auditing in everyday practice can improve our limited knowledge on perioperative diabetes management. Evaluation of preoperative glucose reducing strategies is warranted. Abstract: A growing proportion of patients presenting for surgery have diabetes. Unfortunately, perioperative diabetes protocol compliance is low. Using digitalization of the perioperative environment, an automated reminder in the preoperative assessment platform proved to increase compliance and we advocate its use throughout the perioperative process.